Polyamide biaxially oriented film and packaging material
Patent Information
- Application Number
- JP2020187958
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-11
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2040-11-11
AI Technical Summary
【0015】 本発明によれば、低収縮性、透明性、耐衝撃性のバランスに優れたポリアミド系二軸延伸フィルムを提供することができる。その特徴から、本発明のポリアミド系二軸延伸フィルムは、食料品、医薬衣料品、工業部品等の包装体として好適に用いることができる。
Smart Images

Figure 0007651840000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a biaxially oriented polyamide film having a low hot water shrinkage rate and high impact resistance, and to a package using said film. [Background technology]
[0002] 2. Description of the Related Art Films made of polyamide-based resins are resin materials that are used for a variety of purposes because they are excellent in mechanical properties such as impact resistance and strength, heat resistance, and molding processability such as biaxial orientation. Furthermore, although polyamide-based resins have superior gas barrier properties against oxygen and other gases compared to general-purpose plastics such as polyolefin resins, it is known that the level of gas barrier properties required for long-term storage of contents such as food and pharmaceutical packaging is insufficient. Therefore, polyamide-based resin films that combine mechanical properties, moldability, gas barrier properties, etc. by multilayering with resins with high gas barrier properties such as saponified ethylene-vinyl acetate copolymer (EVOH) and metaxylylenediadipamide (MXD6 nylon) have come to be widely used.
[0003] On the other hand, biaxially stretched films using polyamide resins naturally shrink or heat shrink after stretching, which causes problems such as pitch deviation during printing and delamination during boiling and retort processing. Therefore, as a method for reducing the shrinkage of films caused by biaxial stretching, a method is used in which the film is heat-set in a tenter after biaxial stretching to promote crystallization of the polyamide film. However, although this method can reduce the shrinkage of the film, the molecular chains are fixed, resulting in a film with poor flexibility, which reduces the impact resistance and pinhole resistance, which are characteristics of polyamide biaxially stretched films and are required by the market. Therefore, there is a demand for a polyamide-based biaxially oriented film that has an excellent balance between low shrinkage and impact resistance.
[0004] Patent Document 1 discloses a biaxially stretched polyamide film having excellent gas barrier properties, pinhole resistance, flexibility, and impact resistance and a small shrinkage rate during retorting, characterized in that when a multilayer film consisting of a layer mainly composed of a polyamide resin obtained from metaxylylenediamine and an α,ω-aliphatic dicarboxylic acid having 6 to 12 carbon atoms as main raw materials and a layer mainly composed of an aliphatic polyamide resin is produced by a roll / tenter type sequential biaxial stretching method, the longitudinal stretching roll temperature and stretching ratio, the transverse stretching temperature and stretching ratio, and the heat setting temperature and time are controlled within specific ranges. However, with this technique, the impact resistance of the obtained film is insufficient.
[0005] Patent Document 2 discloses a technology for a polyamide-based film having excellent pinhole resistance and puncture resistance, which contains 86 to 98% by weight of polyamide and 2 to 14% by weight of a flex resistance agent. However, in this technology, when a flex resistance agent that is incompatible with polyamide is blended, there are concerns that the transparency during biaxial stretching may be deteriorated and heat shrinkage may be increased. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2008-94048 A [Patent Document 2] JP 2017-02114 A Summary of the Invention [Problem to be solved by the invention]
[0007] In view of the above circumstances, an object of the present invention is to provide a polyamide-based biaxially stretched film having low shrinkage, transparency and impact resistance, and a packaging material using said film. [Means for solving the problem]
[0008] As a result of intensive investigations aimed at solving the above-mentioned problems, the present inventors have found that the above-mentioned problems can be solved by a polyamide-based biaxially stretched film having at least a polyamide resin layer (A) and a gas barrier resin layer (B), wherein the polyamide resin layer (A) contains 50 to 99 mass % of polyamide 6 and 1 to 50 mass % of a polyamide resin (a) which is a condensation polymer of an aliphatic diamine and an aliphatic dicarboxylic acid and has a heat of fusion of 60 J / g or less, and have completed the present invention as described below.
[0009] The first invention relates to a biaxially stretched polyamide-based film having at least a polyamide resin layer (A) and a gas barrier resin layer (B), characterized in that the polyamide resin layer (A) contains 50 to 99 mass % of polyamide 6 and 1 to 50 mass % of a polyamide resin (a) which is a condensation polymer of an aliphatic diamine and an aliphatic dicarboxylic acid and has a heat of fusion of 60 J / g or less.
[0010] In the first aspect of the present invention, the polyamide resin (a) preferably has hexamethylenediamine in its molecular structure.
[0011] In the first invention, it is preferred that the haze is 5.0% or less, and the hot water shrinkage at 127° C. for 5 minutes is 12.0% or less in both the machine direction and width direction of the film.
[0012] In the first invention, the number of pinholes in the Gelbo flex test under the conditions of 23°C, 3000 bending cycles and 5°C, 500 bending cycles was 4.0 / 481cm. 2 It is preferable that it is less than 1000 .mu.m.
[0013] In the first aspect of the present invention, the puncture impact strength is preferably 1.6 J or more.
[0014] The second invention of the present invention is a package using the biaxially stretched film of the first invention of the present invention. Effect of the Invention
[0015] According to the present invention, it is possible to provide a polyamide-based biaxially stretched film having an excellent balance of low shrinkage, transparency, and impact resistance. Due to this characteristic, the polyamide-based biaxially stretched film of the present invention can be suitably used as a package for food, medicine, clothing, industrial parts, etc. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The present invention will be described in detail below. Note that the "biaxially stretched polyamide film of the present invention" may be referred to as the "film of the present invention," the "polyamide resin layer (A)" as the "layer (A)," and the "gas barrier resin layer (B)" as the "layer (B)." Furthermore, when it is written "X to Y" (X and Y are any numbers), unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as "preferably greater than X" and "preferably smaller than Y".
[0017] <Polyamide resin layer (A)> The polyamide resin layer (A) of the biaxially stretched polyamide film of the present invention contains polyamide 6 and polyamide resin (a) which is a condensation polymer of an aliphatic diamine and an aliphatic dicarboxylic acid and has a heat of fusion of 60 J / g or less. The composition ratio of polyamide 6 to polyamide resin (a) is (50-99)% by mass:(1-50)% by mass (polyamide 6:polyamide resin (a), hereinafter the same), preferably (60-98)% by mass:(2-40)% by mass, more preferably (70-97)% by mass:(3-30)% by mass, when the total amount of polyamide 6 and polyamide resin (a) in layer (A) is taken as 100% by mass. When the composition ratio is in this range, polyamide resin (a) is easily dispersed and distributed evenly in polyamide 6, and impact resistance and low shrinkage can be imparted while maintaining transparency. On the other hand, when polyamide 6 is less than 50% by mass and polyamide resin (a) is more than 50% by mass, film formability and stretchability are significantly deteriorated, and transparency and mechanical properties become insufficient.
[0018] (Polyamide 6) As the polyamide 6 used in the present invention, a known resin obtained by ring-opening polymerization of ε-caprolactam can be used. In terms of film formability, the relative viscosity measured under the conditions of JIS K6920-2:2009, 96% sulfuric acid, is preferably 1.0 to 5.0, more preferably 2.0 to 4.5, and particularly preferably 2.5 to 4.0. Within this range, it is easy to stably co-extrude the layer with a gas barrier resin layer (B) composed of a gas barrier resin such as a saponified ethylene-vinyl acetate copolymer or metaxylenediadipamide, and other layers (C) composed of aliphatic polyamide resins, polyolefin resins, polyester resins, other resins, etc., and there is little flow unevenness due to the viscosity difference between layers. The melting point of the polyamide 6 used in the present invention is preferably 200° C. to 250° C., more preferably 210° C. to 240° C. The heat of fusion of the polyamide 6 is preferably 64 to 70 J / g. When the melting point and heat of fusion of the polyamide 6 are within the above ranges, the heat resistance is excellent, and extrusion moldability and molding into a biaxially stretched film are facilitated.
[0019] (Polyamide resin (a)) The polyamide resin (a) used in the present invention has a heat of fusion of 60 J / g or less and is obtained by a condensation polymerization reaction of an aliphatic diamine and an aliphatic dicarboxylic acid. Polyamide resin (a) is a condensation polymer of aliphatic diamine and aliphatic dicarboxylic acid, generally expressed as "polyamide n,m (n,m are indexes derived from the carbon numbers of the monomers)", and therefore has non-uniform molecular chains in terms of molecular structure compared to polyamide 6. Therefore, compared to when the polyamide resin layer (A) is composed of 100% by mass of polyamide 6, the crystal orientation of layer (A) is relaxed, the shrinkage stress of the film is lowered, and the shrinkage of the film is reduced.
[0020] When the heat of fusion of the polyamide resin (a) is 60 J / g or less, the heat of fusion is relatively lower than that of polyamide 6, and therefore the heat of fusion of the entire layer (A) is lower than when the polyamide resin layer (A) is composed of 100 mass % polyamide 6. In other words, the overall crystallinity of the layer (A) is lower, and the impact resistance of the layer (A) and therefore the impact resistance of the film are improved. The heat of fusion is preferably 58 J / g or less, more preferably 55 J / g or less. The heat of fusion (ΔHm) of polyamide resin was measured using a differential scanning calorimeter (DSC) by heating from 0°C to 250°C at a scanning rate of 10°C / min, holding at 250°C for 1 minute, and then lowering to 0°C at a scanning rate of 10°C / min.The heat of fusion (ΔHm, unit J / g) was then analyzed when the temperature was raised again to 250°C at a scanning rate of 10°C / min.
[0021] As the polyamide resin (a), for example, aliphatic polyamide resins having hexamethylenediamine in the molecular structure such as polyamide 6,66, polyamide 6,10, polyamide 6,12, polyamide 6,66,12, etc., and biomass-derived aliphatic polyamide resins such as polyamide 4,6, polyamide 4,10, polyamide 5,6, polyamide 5,10, polyamide 6,10, polyamide 9,10, polyamide 10,10, polyamide 10,12, etc. are preferable. These may be used alone or in combination of two or more kinds.
[0022] Among them, when a polyamide resin having hexamethylenediamine in its molecular structure is used as the polyamide resin (a), it has high compatibility and affinity with polyamide 6, so that the sea / island dispersion structure of polyamide 6 / polyamide resin (a) in the layer (A) becomes fine, and whitening due to void generation at the sea / island phase interface during biaxial stretching can be suppressed, and the transparency of the film is improved. A biomass-derived polyamide resin is preferable because it not only exhibits the effects of the present invention as the polyamide resin (a), but is also effective in reducing the environmental load. Polyamide 6,10 has hexamethylenediamine in its molecular structure and is derived from biomass as a raw material, and is a resin that combines the advantages of both. Furthermore, polyamide 6,10 is preferable because the resin has a high biomass ratio of 60 to 65%, and therefore has a high efficiency of reducing the environmental load. When a biomass-derived polyamide resin is used, the biomass ratio of the film can be calculated from the composition ratio of the layer (A) and the thickness ratio of the layer (A) to the total thickness of the film. For example, when polyamide 6,10 is used as the polyamide resin (a), the biomass ratio of the film is preferably 0.5 to 40%, more preferably 1 to 30%.
[0023] Among these, polyamide 6,66 (ΔHm 49 J / g), polyamide 6,10 (ΔHm 51 J / g), polyamide 6,12 (ΔHm 52 J / g), and polyamide 6,66,12 (ΔHm 36 J / g) are preferred from the viewpoint that the crystallinity of the resin itself is low, they have good compatibility with polyamide 6, and they contribute to the transparency, low shrinkage, and impact resistance of the film. In particular, polyamide 6,10 is preferred because it has a faster crystallization rate when cooled from a molten state than polyamide 6, and can reduce the crystallinity of the entire polyamide resin layer (A) and suppress the shrinkage rate of the film. Polyamide 6,10 (polyhexamethylenesebacamide) is produced by condensation polymerization of hexamethylenediamine and sebacic acid. Sebacic acid can be produced from plant raw materials such as castor oil extracted from castor bean seeds and 10-hydroxy-12-octadecenoic acid.
[0024] The polyamide resin (a) used in the present invention preferably has a melt flow rate (MFR) of 0.1 to 30 g / 10 min at 230° C. and 2.16 kg weight, more preferably 1 to 20 g / 10 min, and even more preferably 2 to 10 g / 10 min. When the MFR of the polyamide resin (a) is within this range, the compatibility with polyamide 6 is improved, and viscosity unevenness and poor dispersion during extrusion molding can be suppressed.
[0025] (Other ingredients) The polyamide resin layer (A) may contain other resins, thermoplastic elastomers, additives, etc., within the limits not impairing the effects of the present invention. Other resins include semi-crystalline aromatic polyamide resins such as polyamide 12, polyamide 6,6, polyamide 4T, polyamide 5T, polyamide M-5T, polyamide 9T, polyamide 10T, polyamide 11T, polyamide 12T, polyamide MXD6, polyamide PXD6, polyamide MXD10, and polyamide PXD6, and amorphous aromatic polyamide resins such as polyamide PACMT, polyamide PACMI, polyamide PACM12, and polyamide PACM14. Among these, polyamide 12 is preferably used to impart low water absorption and flexibility to the film, and polyamide 6,6 is preferably used to improve the heat resistance, mechanical strength, etc. of the film. In addition, it is preferable to use polyamide MXD6 in the gas barrier resin layer (B) described below and to contain polyamide MXD6 in layer (A) as well, since this improves the interlayer adhesion between layers (A) and (B) and improves the oxygen gas barrier property of the film. The content of other resins in the layer (A) is preferably from 0 to 20% by mass.
[0026] Examples of the thermoplastic elastomer include polyamide-based elastomers, polyester-based elastomers, polystyrene-based elastomers, polyolefin-based elastomers, and acrylic-based elastomers. Examples of polyamide-based elastomers include block copolymers with aliphatic polyamide as a hard segment and polyalkylene ether glycol as a soft segment, which have high affinity with polyamide 6 and polyamide resin (a) and are suitable for imparting flexibility to polyamide-based biaxially stretched films. Among them, PA6-polyethylene glycol (PEG) block copolymer, PA6-polytetramethylene glycol (PTMG) block copolymer, PA11-PEG block copolymer, PA11-PTMG, PA12-PEG block copolymer, and PA12-PTMG block copolymer are preferred, with PA11-PTMG and PA12-PTMG being more preferred. As the polyester-based elastomer, a block copolymer having a polyalkylene ether glycol as a soft segment, particularly one in which a part of the glycol or diol of polybutylene terephthalate is a polyalkylene ether glycol segment, is particularly preferred. The lower limit of the content of the polyalkylene ether glycol segment in the polyamide elastomer or polyester elastomer is preferably 30% by mass, more preferably 40% by mass, and even more preferably 50% by mass, and the upper limit is preferably 90% by mass, more preferably 85% by mass, and even more preferably 80% by mass. A content of the polyalkylene ether glycol segment equal to or less than the above upper limit is preferred in terms of hardness and mechanical strength, while a content of the polyalkylene ether glycol segment equal to or more than the above lower limit is preferred in terms of flexibility and impact resistance. The content of the polyalkylene ether glycol segment can be measured by nuclear magnetic resonance spectroscopy (H 1 -NMR) can be used to calculate the hydrogen atom concentration based on its chemical shift and its content.
[0027] The polyalkylene ether glycol in the polyamide elastomer or polyester elastomer may be modified. Examples of the modifying component include unsaturated carboxylic acid and / or its anhydride such as maleic anhydride, glycidyl acid, amine, epoxy, isocyanate, etc. Among them, elastomers graft-modified with α,β-ethylenically unsaturated carboxylic acid and / or its anhydride such as maleic anhydride are preferred. The modification rate is preferably 0.01 to 10% by mass. The lower limit is more preferably 0.05% by mass or more, and even more preferably 0.1% by mass or more. The upper limit is more preferably 7% by mass or less, and even more preferably 5% by mass or less. The modification rate is H 1 - It can be determined by NMR.
[0028] Examples of polystyrene-based elastomers include styrene-butadiene-styrene block copolymer (SBS), styrene-isoprene-styrene block copolymer (SIS), styrene-ethylene / propylene copolymer (SEP), styrene-ethylene / propylene-styrene block copolymer (SEPS), styrene-ethylene / butylene-styrene block copolymer (SEBS), styrene-ethylene-ethylene / propylene-styrene block copolymer (SEEPS), styrene-isobutylene block copolymer (SIB), and styrene-isobutylene-styrene block copolymer (SIBS). The content of the thermoplastic elastomer in the layer (A) is preferably from 0 to 30% by mass.
[0029] Examples of additives that may be included include heat stabilizers, antioxidants, ultraviolet absorbers, weather resistance agents, lubricants, fillers, nucleating agents, plasticizers, antiblocking agents, antifogging agents, flame retardants, dyes, pigments, stabilizers, coupling agents, and impact resistance improvers.
[0030] <Gas barrier resin layer (B)> The film of the present invention can be imparted with gas barrier properties by providing a layer (B) made of a gas barrier resin, and is useful for preventing deterioration or spoilage of the contents and improving long-term storage stability when used as a packaging material. As the gas barrier resin, known resins can be used, for example, polyvinyl alcohol (PVA)-based resins, saponified ethylene-vinyl acetate copolymer (EVOH)-based resins, semi-aromatic polyamides containing metaxylylenediamine such as polymetaxylylenediadipamide (polyamide MXD6), polyvinylidene chloride (PVDC)-based resins, etc. Among them, in terms of oxygen gas barrier properties and moldability, saponified ethylene-vinyl acetate copolymer (EVOH)-based resins and semi-aromatic polyamides containing metaxylylenediamine are preferred.
[0031] (Saponified ethylene-vinyl acetate copolymer) The ethylene-vinyl acetate copolymer saponified product (EVOH) used in the present invention is a copolymer obtained by saponifying a copolymer of ethylene and vinyl acetate with an alkali catalyst or the like. The ethylene content in the ethylene-vinyl acetate copolymer saponified product is not particularly limited, but from the viewpoint of film formation stability, it is generally preferably 5 mol% or more, more preferably 10 mol% or more, and particularly preferably 20 mol% or more. On the other hand, from the viewpoint of gas barrier properties, the upper limit of the ethylene content is preferably 48 mol% or less, more preferably 38 mol% or less, and even more preferably 30 mol% or less. The saponification degree of the ethylene-vinyl acetate copolymer saponified product is preferably 96% or more, more preferably 98% or more. In the film of the present invention, the ethylene content and saponification degree in the ethylene-vinyl acetate copolymer saponified product are in the above ranges, so that the film formability and gas barrier properties are well balanced, and the film formability and gas barrier properties are well balanced, and the film is suitable for coextrusion with the layer (A) and molding such as biaxial stretching.
[0032] The saponified ethylene-vinyl acetate copolymer may be modified in various ways as necessary. Examples of the modified saponified ethylene-vinyl acetate copolymer include modified ethylene-vinyl acetate copolymers with propylene, isobutene, etc., modified ethylene-vinyl acetate copolymers with at least one α-olefin having 3 to 30 carbon atoms, modified ethylene-vinyl acetate copolymers obtained by graft polymerization of acrylic acid esters, modified ethylene-vinyl acetate copolymers obtained by saponifying a terpolymer consisting of (meth)acrylic acid ester-ethylene-vinyl acetate, and ethylene-vinyl acetate-3,4-diacetoxybutene, modified ethylene-vinyl acetate copolymers in which the hydroxyl groups of the saponified ethylene-vinyl acetate copolymers are modified with cyanoethyl groups, modified ethylene-vinyl acetate copolymers containing polyester grafts obtained by depolymerizing polyester with vinyl alcohol, and modified ethylene-vinyl acetate copolymers obtained by saponifying a copolymer of vinyl acetate-ethylene-silicon-containing olefinic unsaturated monomers. modified ethylene-vinyl acetate copolymer saponified product obtained by saponifying a terpolymer consisting of a pyrrolidone ring-containing monomer-ethylene-vinyl acetate; modified ethylene-vinyl acetate copolymer saponified product obtained by saponifying a terpolymer consisting of acrylamide-ethylene-vinyl acetate; modified ethylene-vinyl acetate copolymer saponified product obtained by saponifying a terpolymer consisting of allyl acetate-ethylene-vinyl acetate; modified ethylene-vinyl acetate copolymer saponified product obtained by saponifying a terpolymer consisting of isopropenyl acetate-ethylene-vinyl acetate; modified ethylene-vinyl acetate copolymer saponified product in which a polyether component is added to the end of a saponified ethylene-vinyl acetate copolymer; modified ethylene-vinyl acetate copolymer saponified product in which a polyether component is added in the form of a graft as a branch polymer of a saponified ethylene-vinyl acetate copolymer; and modified ethylene-vinyl acetate copolymer saponified product in which an alkylene oxide is added to a saponified ethylene-vinyl acetate copolymer. These modified saponified ethylene-vinyl acetate copolymers may be used alone or in combination of two or more, or in combination with a saponified ethylene-vinyl acetate copolymer.
[0033] (Semi-aromatic polyamide containing meta-xylylenediamine) Examples of semi-aromatic polyamides containing metaxylylene diamine that can be used in the present invention include homopolymers such as polymetaxylylene adipamide (polyamide MXD6), polymetaxylylene pimelamide, polymetaxylylene suberamide, polymetaxylylene azelamide, polymetaxylylene sebacamide, and polymetaxylylene dodecanediamide, as well as metaxylylene / paraxylylene adipamide copolymers, metaxylylene / paraxylylene pimelamide copolymers, metaxylylene / paraxylylene suberamide copolymers, metaxylylene / paraxylylene azelamide copolymers, and metaxylylene / paraxylylene sebacamide copolymers. Examples of such copolymers include taxylylene / paraxylylenesebacamide copolymer, metaxylylene / paraxylylenedodecanediamide copolymer, and copolymers obtained by copolymerizing these homopolymers or copolymer components with aliphatic diamines such as hexamethylenediamine, alicyclic diamines such as piperazine, aromatic diamines such as para-bis-(2-aminoethyl)benzene, aromatic dicarboxylic acids such as terephthalic acid, lactams such as ε-caprolactam, ω-aminocarboxylic acids such as aminoheptanoic acid, aromatic aminocarboxylic acids such as para-aminomethylbenzoic acid, etc. Among these, polymetaxylyleneadipamide (polyamide MXD6) is preferred from the viewpoints of gas barrier properties and moldability.
[0034] Polymetaxylyleneadipamide (polyamide MXD6) refers primarily to the polymerization product of metaxylylenediamine and adipic acid. When the diamine component constituting the polymetaxylylene adipamide is taken as 100 mol %, metaxylylene diamine accounts for 70 mol % or more, preferably 80 mol % or more, and more preferably 90 mol % or more. Although it may contain 30 mol % or less of isomers such as orthoxylylene diamine and paraxylylene diamine, or aliphatic diamines having 6 to 12 carbon atoms, it is preferable that they are not contained if possible from the viewpoint of gas barrier property and heat resistance. When the dicarboxylic acid component constituting the polymetaxylylene adipamide (polyamide MXD6) is taken as 100 mol %, 70 mol % or more, preferably 80 mol % or more, and more preferably 90 mol % or more of the dicarboxylic acid is adipic acid. The polyamide MXD6 may contain 30 mol % or less of an aliphatic dicarboxylic acid having 7 to 12 carbon atoms, an aromatic dicarboxylic acid such as terephthalic acid or isophthalic acid, or a cyclic aliphatic dicarboxylic acid such as 1,4-cyclohexanedicarboxylic acid, but from the viewpoints of gas barrier property and stretchability, it is preferable that these are not contained if possible.
[0035] (Other ingredients) The gas barrier resin layer (B) can contain a thermoplastic elastomer within a range that does not impair the effects of the present invention. By containing a thermoplastic elastomer, it is possible to improve the flexibility of the gas barrier resin layer (B) and improve the pinhole resistance of the film. As the thermoplastic elastomer, the types that can be contained in the polyamide resin layer (A) described above can be used in the same way. When the layer (B) is taken as 100% by mass, the content of the thermoplastic elastomer is preferably 20% by mass or less, more preferably 1 to 15% by mass. By making the content of the thermoplastic elastomer 20% by mass or less, the deterioration of the gas barrier property and transparency of the film can be suppressed, and the generation of gel during film formation can be suppressed, which is preferable in terms of film productivity.
[0036] <Layer configuration> The film of the present invention may have at least a polyamide resin layer (A) and a gas barrier resin layer (B). When a plurality of layers (A) are provided, the layers (A) may have the same composition or different compositions. The same applies when a plurality of layers (B) are provided. In addition to the layers (A) and (B), another layer (C) may be provided. The order of the layers is not particularly limited, but for example, a two-layer structure of [A / B], a three-layer structure of [A / B / A], [A / B / C], [A / C / B], and [C / A / B], and a five-layer structure of [A / A / B / A / A], [A / C / B / C / A], [C / A / B / A / C], and [A / B / C / B / A] are preferred in terms of film formation stability.
[0037] The components of the other layer (C) are not particularly limited. However, when the layer (C) is disposed between the layer (A) and the layer (B), it is preferable to include a component common to the layer (A) and / or the layer (B) or to use an adhesive resin in order to improve the interlayer adhesion. When layer (C) is provided on the outside of layer (A), in other words, on the surface layer side of the film, it is preferable to use an aliphatic polyamide such as polyamide 6, polyamide 6,6 or polyamide 6,66 in order to improve the pinhole resistance and abrasion and wear resistance of the film.
[0038] The total thickness of the film of the present invention is not particularly limited, but considering, for example, processability and practicality, the lower limit is preferably 5 μm or more, more preferably 10 μm or more, and even more preferably 12 μm or more. The upper limit is preferably 50 μm or less, more preferably 30 μm or less, and even more preferably 25 μm or less. If the total thickness is within the above range, the film has good rigidity as a polyamide biaxially stretched film, is excellent in mechanical properties such as bending pinhole resistance and impact resistance, and is also excellent in gas barrier properties. From the viewpoints of pinhole resistance and oxygen gas barrier property, it is preferable that the thickness ratio of layer (A) is 25 to 90% and the thickness ratio of layer (B) is 10 to 70% of the total film thickness (100%). When there are multiple layers (A) and / or layers (B), the ratio is the ratio of the total thickness of layer (A) or layer (B) to the total thickness. The thickness of each of the layers (A), (B), and (C) is not particularly limited, but is preferably 1 to 15 μm, more preferably 2 to 10 μm, and even more preferably 3 to 8 μm. When there are a plurality of layers (A), (B), and (C), each layer may have a different thickness or the same thickness.
[0039] The film of the present invention may be subjected to surface treatment or surface processing such as printing, coating, vapor deposition, etc. In addition, it may be used by laminating other resin layers such as polyolefin or polyester, other films or adhesive layers, metal foils, paper, etc., and the lamination method may be a known method, such as dry lamination, wet lamination, sand lamination, extrusion lamination, etc. In addition, during lamination, the surface of the film of the present invention may be subjected to surface treatment such as corona discharge or anchor coating. Furthermore, when the film of the present invention is used as a packaging material, from the viewpoint of maintaining the quality of the contents and preventing spoilage, the gas barrier property and moisture resistance can be further improved by laminating a gas barrier resin layer, or by vapor-depositing aluminum, silicon oxide, alumina, diamond-like carbon, or the like, or by applying a gas barrier coating agent such as a polyvinyl alcohol (PVA)-based resin or a polyvinylidene chloride (PVDC)-based resin.
[0040] <Manufacturing method> The film of the present invention may be any biaxially stretched film, and may be produced by a known method. The raw materials, polyamide 6 of layer (A), polyamide resin (a), and gas barrier resin of layer (B), are all highly hygroscopic resins, and if hygroscopic resins are used, water vapor and oligomers are generated during thermal melting and extrusion, which inhibits film formation. Therefore, when preparing the raw materials, it is preferable to dry the resins in advance to reduce the moisture content to 0.1% by mass or less.
[0041] The resins are fed into extruders for each layer, and the molten resins are joined in a feed block, or a multi-manifold flat die, or an annular die, and then co-extruded as a multilayer film. The resulting film is then quenched to obtain a flat or annular unstretched film.
[0042] Next, the unstretched film is biaxially stretched in the flow direction (machine direction, MD) of the film and in the width direction (transverse direction, TD) perpendicular thereto, using a known method such as tenter-type sequential biaxial stretching, tenter-type simultaneous biaxial stretching, or tubular-type simultaneous biaxial stretching. For example, in the case of the tenter-type sequential biaxial stretching method, the unstretched film can be produced by heating the unstretched film to a temperature range of 40 to 100°C, stretching it in the machine direction using a roll-type machine-type stretching machine, and then stretching it in the transverse direction within a temperature range of 60 to 140°C using a tenter-type transverse stretching machine. In addition, in the case of the tenter-type simultaneous biaxial stretching method or the tubular-type simultaneous biaxial stretching method, the film can be produced by simultaneously stretching it in the machine and transverse directions, for example, in a temperature range of 60 to 200°C. The stretching ratio is preferably 2.0 to 5.0 times, more preferably 2.5 to 4.5 times, in each of the machine direction (machine direction, MD) and width direction (transverse direction, TD) of the film. When the stretching ratio in each of the biaxial stretching directions is 2.0 times or more, stretch orientation proceeds and mechanical properties such as film strength become good, and when the stretching ratio is 5.0 times or less, the film is less likely to break during stretching, and productivity is good.
[0043] Furthermore, in order to improve the dimensional stability of the film, the biaxially stretched film can be heat-set. The heat-setting temperature is preferably 200°C to 225°C, more preferably 205°C to 220°C. This makes it possible to obtain a biaxially stretched film having good dimensional stability at room temperature and any desired heat shrinkability, impact resistance, and bending pinhole resistance. Furthermore, the film of the present invention can improve low shrinkability and impact resistance by including polyamide resin (a) in layer (A). In order to relax the stress of crystallization shrinkage due to heat setting, a relaxation treatment can be carried out in the width direction during heat setting in the range of 0 to 15%, preferably 3 to 10%. After the relaxation treatment, the film can be re-stretched in the width direction by 2 to 9%, preferably 3 to 7%, and more preferably 4 to 7% at a temperature of 140° C. to 200° C. If the re-stretching temperature is within the above range, an appropriate stress during stretching is obtained, resulting in homogeneous stretching and making it easier to achieve a uniform transverse shrinkage rate in the width direction.
[0044] <Film properties> (Hot water shrinkage rate) The hot water shrinkage rate of the present film at 95°C for 5 minutes and at 127°C for 5 minutes is preferably 0.1% to 12.0% in both the machine direction (MD) and the transverse direction (TD). The upper limit is more preferably 10.0% or less. The lower limit is more preferably 0.3% or more, and even more preferably 0.5% or more. When the hot water shrinkage rate is 0.1% or more, the biaxially stretched film can easily have both impact resistance, pinhole resistance at bending, and low shrinkage. Also, when the hot water shrinkage rate is 12.0% or less, shrinkage due to heat applied in post-processing such as printing, lamination, and bag making is unlikely to occur, and misalignment during printing, wrinkles during lamination, and distortion of bag products can be suppressed. Generally, in a polyamide-based biaxially oriented film, a high hot water shrinkage rate is flexible and advantageous in terms of low-temperature pinhole resistance, but the film mechanical strength and the above-mentioned post-processability tend to be insufficient. In the case of the film of the present invention, however, by mixing polyamide resin (a) with polyamide 6 in the polyamide-based resin layer (A), the orientation of polyamide 6 is relaxed while maintaining the strength of the film, so that even with a low hot water shrinkage rate, there is an advantage in that the film mechanical strength, impact resistance, and pinhole resistance due to bending are easily sufficient. The hot water shrinkage can be measured by the method described in the evaluation of the examples below.
[0045] (shock resistance) The impact resistance of the film of the present invention can be evaluated by the puncture impact strength when the penetration part makes a hole in a film test piece, and is preferably 1.6 J or more, more preferably 1.8 J or more, and even more preferably 2.0 J or more. If the puncture impact strength is within this range, the film has excellent impact resistance and is good in that it is difficult to make a hole when used as a packaging material. The impact resistance of the film of the present invention is measured by the impact hole opening strength test of JIS P8134: 1998. The stand of the device is installed on a solid foundation so as not to cause loss of work, and the pendulum has an arm in a 90-degree arc, a penetrating part is attached to the tip of the arm, and it can oscillate freely.
[0046] (transparency) The film of the present invention preferably has a haze of 5.0% or less, more preferably 4.5% or less, and even more preferably 3.0% or less. When the haze value is within this range, the film has excellent transparency, and has good design properties and visibility of contents when used as a packaging film. Haze is measured based on JIS K7136:2000.
[0047] (Tensile stress at break, tensile elongation at break) The film of the present invention has excellent mechanical strength, and the tensile stress at break is preferably in the range of 100 to 400 MPa in both the machine direction (MD) and the transverse direction (TD), with the lower limit being more preferably 150 MPa or more, and even more preferably 200 MPa or more. If the film has a tensile stress at break in this range, when the contents are packaged, the film is less likely to develop pinholes or break due to bending while maintaining its rigidity. The tensile elongation at break is preferably 80% to 300% in either the machine direction (MD) or the transverse direction (TD), and the lower limit is more preferably 100% or more. In addition, if both the machine direction (MD) and the transverse direction (TD) are in the above range, the film has excellent toughness, which is more preferable. The tensile stress at break and the tensile elongation at break are measured under the conditions of JIS K7127:1999, a test speed of 200 mm / min, and 23°C.
[0048] (Bending pinhole resistance) The film of the present invention was subjected to a flex test using a Gelbo flex tester under the following conditions: 3,000 flexes at 23°C and 50% relative humidity, and 500 flexes at 5°C and 50% relative humidity, and the number of pinholes that occurred was counted. Three tests were performed under each condition, and the average value was calculated. The number of pinholes was 4.0 / 481 cm under all conditions. 2 Less than 3.0 pieces / 481 cm is preferable. 2 Less than 2.0 pieces / 481cm is more preferable. 2 Less than 1.0 piece / 481cm is more preferable. 2The following is particularly preferred. In general, the lower the environmental temperature, the less flexibility the film has, so it is desirable to have fewer pinholes under low temperature conditions. 2 If the thickness is less than this, pinholes are less likely to occur due to bending of the film during transportation and storage of the package or collisions between packages, and oxidative deterioration of the contents due to a decrease in gas barrier properties is more easily suppressed.
[0049] (Oxygen gas barrier properties) The film of the present invention has an oxygen permeability of 10 cc / m under conditions of 23°C and 50% relative humidity. 2 / 24h / atm or less is preferable, and 5cc / m 2 / 24h / atm or less is more preferable, and an even lower value is desirable. 2 / 24h / atm or less is preferable because the film can maintain sufficient oxygen gas barrier properties as a packaging film to prevent deterioration of the contents and keep them fresh.
[0050] (Biomass ratio) When a biomass-derived polyamide resin is used, the biomass ratio (%) of the entire film can be calculated from the biomass ratio of the resin, the composition ratio of the layer containing the resin, and the thickness ratio of the layer to the total thickness of the film. The biomass ratio of the entire film is preferably 0.5 to 40%, more preferably 1 to 30%. EXAMPLES
[0051] The present invention will be specifically described below using examples, but the present invention is not limited to these.
[0052] <Ingredients> The abbreviations, components, physical properties, etc. of the resins used in the examples and comparative examples are as follows. The relative viscosity of the polyamide resin was measured under the conditions of JIS K6920-2:2009, 96% sulfuric acid. The heat of fusion (ΔHm) of polyamide resin was measured using a differential scanning calorimeter (DSC) by heating from 0°C to 250°C at a scanning rate of 10°C / min, holding at 250°C for 1 minute, and then lowering to 0°C at a scanning rate of 10°C / min.The heat of fusion (ΔHm, unit J / g) was then analyzed when the temperature was raised again to 250°C at a scanning rate of 10°C / min.
[0053] (Polyamide resin) n1: Polyamide 6, relative viscosity 3.4, melting point 222.5℃, ΔHm 68J / g a1: Polyamide 6,10, ΔHm 51J / g, biomass content 62% a2: Polyamide 6,66, ΔHm 49J / g (Other resins) e1: Polyamide 12-PTMG block copolymer, PTMG 70% by mass (Gas barrier resin) b1: Ethylene-vinyl acetate copolymer saponification product (EVOH), ethylene content 25 mol% b2: Polymetaxylylene adipamide (polyamide MXD6)
[0054] <Film production> (Example 1, Comparative Example 1) The resin composition for the surface layers (layer (A) and layer (C)), which was made by mixing the raw materials in the mass ratio shown in Table 1, was fed into an extruder with a diameter of 40 mm, and the resin composition for the gas barrier layer (layer (B)) was fed into an extruder with a diameter of 32 mm. The respective molten resin compositions were distributed in a distribution block and multilayered in a co-extrusion T-die to extrude a molten film, which was then quenched on a cooling roll at 30°C to produce an unstretched multilayer film. In Example 1 and Comparative Example 1, a multilayer film having a three-layer structure of "surface layer / gas barrier resin layer / surface layer" was used. The obtained unstretched multilayer film was stretched 3.0 times in the longitudinal direction using a roll-type longitudinal stretching machine at 55° C., then stretched 4.0 times in the transverse direction using a tenter-type transverse stretching machine at 120° C., and then heat-set at 215° C. Thereafter, it was cooled to room temperature, both ends corresponding to the gripping parts of the clips were trimmed, and the trimmed film was wound into a roll to obtain a biaxially stretched multilayer film with a total thickness of 15.0 μm. The thickness of each layer was measured by cutting the film vertically and observing it with a microscope. The obtained film was evaluated as follows. The results are shown in Table 1.
[0055] (Examples 2 to 4, Comparative Examples 2 to 3) The resin compositions for the surface layers (layer (A) and layer (C)), which were made by mixing the raw materials in the mass ratio shown in Table 1, were fed into extruders with a diameter of 65 mm, and the resin composition for the gas barrier resin layer (layer (B)) was fed into an extruder with a diameter of 50 mm. The molten resin compositions were then distributed in a distribution block and multilayered in a co-extrusion T-die, and the molten films were extruded and rapidly cooled on a cooling roll at 30°C to produce unstretched multilayer films. In Example 2 and Comparative Example 2, the multilayer film had a three-layer structure of "surface layer / gas barrier resin layer / surface layer," while in Examples 3 and 4 and Comparative Example 3, the multilayer film had a five-layer structure of "surface layer / intermediate layer / gas barrier layer / intermediate layer / surface layer." The obtained unstretched multilayer film was stretched 3.0 times in the longitudinal direction using a roll-type longitudinal stretching machine at 55° C., then stretched 3.5 times in the transverse direction using a tenter-type transverse stretching machine at 120° C., and then heat-set at 215° C. Thereafter, it was cooled to room temperature, both ends corresponding to the gripping parts of the clips were trimmed, and the trimmed film was wound into a roll to obtain a polyamide-based biaxially stretched film with a total thickness of 15.0 μm. The thickness of each layer was measured by cutting the film vertically and observing it with a microscope. The obtained film was evaluated as follows. The results are shown in Table 1.
[0056] <Evaluation> (1) Hot water shrinkage At three points at both ends and the center of the film, a 120 mm square test piece was cut out parallel to the machine direction (machine direction, MD) and width direction (transverse direction, TD) of the film, and three reference lines of more than 100 mm were drawn in the machine and width directions of the sample. The test piece was left to stand for 24 hours in an atmosphere of 23°C and 50% relative humidity, and the length of the reference lines was measured, and the length before heat treatment was designated F. The test piece was then immersed in hot water at 95°C for 5 minutes, or autoclaved at 127°C for 5 minutes. After that, the test piece was left to stand for 30 minutes in an atmosphere of 23°C and 50% relative humidity, and the length of the reference lines was measured, and the length after heat treatment was designated G. The following formula was used to calculate the average value of the three hot water shrinkage rates (unit: %) in the machine direction and width direction of each test piece, and the hot water shrinkage rates (unit: %) in the machine direction and width direction of the film were calculated from the average value of both ends and the center of the film. (Formula) (FG) / F×100 (%)
[0057] (2) Impact resistance The puncture impact strength (unit: J) was measured by the impact hole opening strength test of JIS P8134:1998. The stand of the device was set on a solid foundation so as not to cause loss of work, and the pendulum had an arm in a 90 degree arc, with a penetrating part attached to the tip of the arm, allowing it to vibrate freely.
[0058] (3) Transparency Haze (unit: %) was measured in accordance with JIS K7136:2000.
[0059] (4) Tensile stress at break, tensile elongation at break Based on JIS K7127:1999, the tensile breaking stress (unit: MPa) and tensile breaking elongation (unit: %) in the machine direction and transverse direction (MD direction, TD direction) were measured at a test speed of 200 mm / min and 23°C.
[0060] (5) Pinhole resistance due to bending A test piece measuring 20cm x 28cm was cut out from the film and left to stand for 24 hours or more under the conditions of the specified temperature and relative humidity of 50% shown below to adjust the temperature and humidity. The bending test was repeated as follows using a Gelbo Flex Tester No. 901 manufactured by Rigaku Kogyosha, which complies with the MIL-B-131C standard, and the test piece was subjected to a bending test of 481cm. 2 The number of pinholes per unit area was counted. The film was rolled into a cylinder with a length of 20 cm and a circumference of 28 cm, and one end of the rolled cylindrical film was fixed to the outer periphery of the disk-shaped fixed head of the tester, and the other end was fixed to the outer periphery of the disk-shaped movable head of the tester. The fixed head and the movable head were opposed to each other with a distance of 17.5 cm. Next, the movable head was rotated 440° while approaching the fixed head along the axis of both heads facing each other in parallel 8.8 cm, then moved straight forward 6.3 cm without rotating, and then these operations were reversed, and the bending test was performed a predetermined number of times at a speed of 40 times per minute. After that, the area of the 17.5 cm x 27.5 cm film excluding the fixed head and the part fixed to the outer periphery of the movable head was 481 cm. 2 Number of pinholes in the area (unit: pcs / 481cm 2 ) was measured by applying a voltage of 1 kV using a pinhole tester TRD model manufactured by Sanko Electronics Laboratory. The temperature, humidity and number of bending tests were performed under two conditions: (i) a temperature of 5° C., a relative humidity of 50%, and a number of bending cycles of 500; and (ii) a temperature of 23° C., a relative humidity of 50%, and a number of bending cycles of 3,000.
[0061] (6) Oxygen gas barrier properties Oxygen permeability (unit: cc / (m) at 23°C and 50% relative humidity according to JIS K-7126 B method 2 ·24h·atm) was measured.
[0062] (7) Biomass ratio The biomass degree of each film was calculated from the biomass degree of polyamide 6,10(a1), which is a polyamide resin derived from biomass and condensation polymerized with sebacic acid made from castor oil extracted from castor beans, the composition ratio of the layer containing the resin, and the thickness ratio of the layer to the total thickness of the film.
[0063] [Table 1]
[0064] Example 1 contained polyamide 6,66, which is a flexible polyamide condensation polymer having a low heat of fusion, in the surface layer, and had a low hot water shrinkage rate at 127° C. for 5 minutes, as compared with Comparative Example 1.
[0065] Example 2 contained polyamide 6,10 in the surface layer and had a smaller hot water shrinkage at 127°C for 5 minutes than Comparative Example 2. Similarly, Example 3 contained polyamide 6,10 in the surface layer and had a smaller hot water shrinkage at 127°C for 5 minutes than Comparative Example 3. This is believed to be because the crystallization of the entire layer (A) progressed easily due to the mixture of polyamide 6 and polyamide 6,10, which has a fast crystallization rate, in layer (A). In addition, polyamide 6,10 has a smaller heat of fusion and a lower degree of crystallization than polyamide 6, so that the puncture impact strength was improved and impact resistance was imparted to the biaxially stretched film.
[0066] In Example 4, polyamide 6,10 and polyamide 6,66, which are flexible polyamide condensation polymers with low heat of fusion, were mixed in the intermediate layer between the surface layer and the gas barrier resin layer (B), and the hot water shrinkage rate was lower and impact resistance was improved compared to Comparative Example 3. [Industrial Applicability]
[0067] The film of the present invention is a polyamide-based biaxially oriented film that combines low shrinkage, transparency, and impact resistance, and can be suitably used for packaging food, medicine, clothing, industrial parts, and the like.
Claims
1. In a film having at least a polyamide resin layer (A) and a gas barrier resin layer (B), the gas barrier resin layer (B) contains a saponified ethylene-vinyl acetate copolymer (EVOH)-based resin and / or a semi-aromatic polyamide containing metaxylylenediamine, the polyamide resin layer (A) contains 50 to 99% by mass of polyamide 6 and 1 to 50% by mass of a polyamide resin (a) which is a condensation polymer of an aliphatic diamine and an aliphatic dicarboxylic acid and has a heat of fusion of 60 J / g or less; A polyamide-based biaxially oriented film characterized in that the haze is 5.0% or less, the hot water shrinkage rate at 127°C for 5 minutes is 12.0% or less in both the film flow direction and width direction, and the puncture impact strength is 1.6 J or more.
2. The polyamide-based biaxially stretched film according to claim 1 , wherein the polyamide resin (a) has hexamethylenediamine in its molecular structure.
3. 3. The polyamide-based biaxially stretched film according to claim 1, wherein the thickness of the gas barrier resin layer (B) is 10 to 70% of the total thickness of the film, the total thickness being 100%.
4. The number of pinholes in the Gelbo Flex test under both the 23°C, 3000 bending conditions and the 5°C, 500 bending conditions was 4.0 / 481cm 2 The polyamide-based biaxially stretched film according to any one of claims 1 to 3, wherein the stretching ratio is less than 1.
5. A package using the biaxially stretched film according to any one of claims 1 to 4.
Citation Information
Patent Citations
Mono- and multi-layer thermoplastic film and polyamide blend contained therein
EP1029896A1
JP1975068084A
Biaxially oriented polyamide film and production thereof
JP1996047972A
Polyamide film excellent in bending fatigue resistance
JP2002166512A
High-adhesion gas barrier transparent film and laminate using the same
JP2007130865A